The Tax Optimization Strategy Of Tourism Sector To Increase Banyuwangi Regency’s Income - Masetya Mukti Mukti; Jemi Cahya Adi Wijaya; Ayu Wanda Febrian (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Abstract Purpose: Banyuwangi Regency is intensively optimizing the tourism sector that has enormous natural and cultural potential. The tourism sector has a broad impact (multiplier effect) felt by all layers of businesses, including businesses in the entertainment industry, hospitality and restaurants. These three business sectors will directly affect income through the tourism sector's local tax. The purpose of this study is determine the relationship of the tourist visitation number to the entertainment tax of Banyuwangi Regency, to find out the relationship of the tourist visitation number to the hotel tax of Banyuwangi Regency, to determine the relationship of the tourist visitation number to the restaurant tax of Banyuwangi Regency. Research methods: The analytical method used in this study is Product Moment Correlation Analysis. Results and discussions: The results of this study indicate that the relationship of the Tourist visitation Number (X1) to the Entertainment Tax (Y1) obtained by Pearson product moment value is 0.938 (Very Strong). The relationship of the Tourist visitation Number (X1) to the Hotel Tax (Y2) obtained by Pearson product moment value is 0.955 (Very Strong). The relationship of the Tourist visitation Number (X1) to Restaurant Tax (Y3) obtained by Pearson product moment value from the Correlation Coefficient is 0.889 (Very Strong). Conclusion: The Three tourism taxes had positive correlations with the Tourist visitation Keywords: optimizing, tourism sector, tax, hospitality